Simulasi Antena Mikrostrip H- Shaped Planar Array 4 Elemen Menggunakan Circular Slot Dengan Pencatuan Microstrip Line Untuk Aplikasi CPE Fixed Wimax Pada Frekuensi 3,5 GHZ (3,4-3,6 GHZ) - Yoga Yusfarino; Eri Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
WiMAX technology has high data transfer speed, large access range and mobility capability. To access the fixed WiMAX network required Costumer Premise Equipment (CPE). CPE require a little dimension antenna and integrated it easily. Therefore, microstrip antenna is a good candidate for this application. In this final project designed of 4 elements planar array microstrip antenna using H-shaped with circular slot for CPE fixed WiMAX applications in 3.5 GHz (3.4-3.6 GHz). The substrates used are FR4 with value of relativity permittivity 4.4 and Duroid with value of relativity permittivity 2.2 using microstrip line feed techniques. To determine the dimensions of the antenna before it designed, performed theoretical calculation first. For this antenna simulation process, the authors use the Ansoft HFSS 13.0. The results of designed showed that antenna works at a frequency of 3.3786-3.6106  GHz using FR4 and 3.383-3.6149 GHz using Duroid at VSWR ≤ 1,9 with gain are 4.7083 dB and 8.486 dB.  Keyword: CPE fixed WiMAX, planar array, VSWR, gain